2008
DOI: 10.1021/bi7025358
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Diversity of Extended Hammerhead Ribozymes

Abstract: Chimeras of the well characterized minimal hammerhead 16 and nine extended hammerheads derived from natural viroids and satellite RNAs were constructed with the goal of assessing whether their very different peripheral tertiary interactions modulate their catalytic properties. For each chimera, three different assays were used to determine the rate of cleavage and the fraction of full length hammerhead at equilibrium and thereby deduce the elemental cleavage (k 2 ) and ligation (k -2 ) rate constants. The nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…Compared with the G17 variants, however, there is no clear trend, because loop variants appear to be tolerated better in PLMVd, similarly in Xetr2 and variably in Ara1 (Supplemental Fig. 1; Table 1), in line with earlier observations of idiosyncrasy in the catalytic activity of individual HHRz motifs (Przybilski and Hammann 2007a;Shepotinovskaya and Uhlenbeck 2008).…”
Section: The Tolerance Of G17 Varies Among Different Hhrz Motifssupporting
confidence: 79%
See 1 more Smart Citation
“…Compared with the G17 variants, however, there is no clear trend, because loop variants appear to be tolerated better in PLMVd, similarly in Xetr2 and variably in Ara1 (Supplemental Fig. 1; Table 1), in line with earlier observations of idiosyncrasy in the catalytic activity of individual HHRz motifs (Przybilski and Hammann 2007a;Shepotinovskaya and Uhlenbeck 2008).…”
Section: The Tolerance Of G17 Varies Among Different Hhrz Motifssupporting
confidence: 79%
“…Several studies have indicated a great variation of tertiary interacting sequences in individual HHRz motifs (Przybilski and Hammann 2007a;Shepotinovskaya and Uhlenbeck 2008), although recurrent signatures were also observed (Dufour et al 2009). The variability of tertiary interacting motifs became even further apparent in several recent database searches for novel HHRz motifs carried out in this and other laboratories Rojas et al 2000;Gräf et al 2005;Przybilski et al 2005;Martick et al 2008;De la Peña and Garcia-Robles 2010;Jimenez et al 2011;Perreault et al 2011;Seehafer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such differences may be due to variations in the protocols used for analyzing cleavage activity (Stage-Zimmermann and Uhlenbeck 1998) and/or be true evidence for the catalytic diversity of extended hammerhead ribozymes (Shepotinovskaya and Uhlenbeck 2008). Regardless, our work now establishes a fourth extended hammerhead particularly suitable for biophysical studies, as demonstrated in the following.…”
mentioning
confidence: 72%
“…The interaction between stems I and II was observed among many different HHRs, as was the case of the two terminal loops in type III viroid and plant HHRs (De la Peña et al 2003;Khvorova et al 2003;Przybilski et al 2005;Shepotinovskaya and Uhlenbeck 2008), and between internal and terminal loops in type I S. mansoni HHRs ( Fig. 3A; Canny et al 2004;Martick and Scott 2006).…”
Section: Stem I-ii Tertiary Interaction and Unusual Variantsmentioning
confidence: 87%